95 YEAR ANNIVERSARY OF THE ST. PETERSBURG RESEARCH INSTITUTE OF PHTHISIOPULMONOLOGY: MAIN AREAS OF RESEARCH IN TUBERCULOSIS PREVENTION, DIAGNOSTICS AND TREATMENT OVER THE LAST DECADE - P. K. Yablonsky; A. A. Starshinova (Туберкулез и болезни лёгких)
.